Analisis Penerapan Laporan Biaya Lingkungan di Rumah Sakit Panti Nirmala Malang - Lanawati, Lilis; Parawiyati; Sihwahjoeni; Priyo Widodo, Puguh (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2025)
This study aims to analyze the implementation of environmental cost reporting at Panti Nirmala Hospital, Malang. Using a qualitative descriptive approach, it examines the identification, calculation, and management of environmental costs. Data were collected through interviews with finance and environmental department leaders, document reviews of environmental cost and financial reports, and direct observations at the hospital. Thematic analysis was applied to assess the implementation of environmental costs.Â The findings reveal that environmental activities at Panti Nirmala Hospital include waste management and environmental health initiatives. However, the hospital has not adopted environmental accounting as per existing theories and does not produce dedicated environmental cost reports. Instead, environmental costs are recorded under building maintenance, operational, and office cost accounts in general financial reports. Cost allocation is based on prior-year expenses, revenue targets, and inflation estimates.Â The COVID-19 pandemic significantly increased waste management costs due to higher usage of personal protective equipment and disposable medical devices, despite a sharp decline in patient visits. These findings highlight the need for systematic environmental cost reporting to better support hospital environmental management and financial accountability.